2019
DOI: 10.1021/acs.biochem.9b00507
|View full text |Cite
|
Sign up to set email alerts
|

Divalent Cations and the Divergence of βγ-Crystallin Function

Abstract: The βγ-crystallin superfamily contains both β- and γ-crystallins of the vertebrate eye lens and the microbial calcium-binding proteins, all of which are characterized by a common double-Greek key domain structure. The vertebrate βγ-crystallins are long-lived structural proteins that refract light onto the retina. In contrast, the microbial βγ-crystallins bind calcium ions. The βγ-crystallin from the tunicate Ciona intestinalis (Ci-βγ) provides a potential link between these two functions. It binds calcium with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(71 citation statements)
references
References 97 publications
5
65
1
Order By: Relevance
“…Following studies have continue to investigate the aggregation process due to high concentration of metals (Domínguez-Calva et al, 2018;Ramkumar et al, 2018). In the case of γS-crystallin it was also found that some cations induce the aggregation formation by interacting with cysteine and methonine residues (Roskamp et al, 2019). Nevertheless, it is unlikely that proteins in the lens would be suddenly in contact with a high concentration of metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Following studies have continue to investigate the aggregation process due to high concentration of metals (Domínguez-Calva et al, 2018;Ramkumar et al, 2018). In the case of γS-crystallin it was also found that some cations induce the aggregation formation by interacting with cysteine and methonine residues (Roskamp et al, 2019). Nevertheless, it is unlikely that proteins in the lens would be suddenly in contact with a high concentration of metal ions.…”
Section: Introductionmentioning
confidence: 99%
“…Deamidation and oxidation (in the presence of GSSG), as occurs in the aging lens, together enhance the aggregation of γS. There are seven cysteine residues in γS of which four are buried with low solvent‐accessible surface area (1–2%) and three have high accessibility, particularly C24 (21–77%) 36,39 . Of the buried cysteine residues, C36, C82, and C114 become more accessible in the deamidated mimics, while one of the accessible cysteine residues, C26, becomes less accessible 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The modification levels in aged γS range from 25–60% at N14, 50–80% at N76, and 20–90% at N143 6,21,29,30,33,34 . These levels of deamidation correlate with their surface accessibility, that is, the labile polar Asn residues at positions 14, 76, and 143, have solvent exposures of ~55, 58, and 60%, respectively 35,36 . Their location is indicated on the solution NMR‐derived structure of γS in Figure 1 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following studies have continue to investigate the aggregation process due to high concentration of metals (Domínguez-Calva et al, 2018;Ramkumar et al, 2018). In the case of γS-crystallin it was also found that some cations induce the agragation formation by interacting with cysteine and methonine residues (Roskamp et al, 2019). Nevertheless, it is unlikely that proteins in the lens would be suddenly in contact with a high concentration of metal ions.…”
Section: Introductionmentioning
confidence: 99%